2012
DOI: 10.1007/s00335-012-9412-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of multiple births in low ovulating mammalian species

Abstract: In mammals, litter size is a highly variable trait. Some species such as humans or cattle are monotocous, with one or sometimes two newborns per birth, whereas others, the polytocous species such as mice or pigs, are highly prolific and often produce a dozen newborns at each farrowing. In monotocous species, however, two or three newborns per birth may sometime be unwanted. In more polytocous species such as sheep or pigs, litter size is studied in order to increase livestock prolificacy. By contrast, twinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 109 publications
0
29
0
1
Order By: Relevance
“…Genetic studies have indicated that LS and OR can be genetically determined by the action of single genes with a major effect, named fecundity (Fec) genes [38]. All the three Fec genes discovered so far belong to the TGFß superfamily: BMPR1B gene ( FecB ) located on OAR6 [18], [19], [20], GDF9 gene ( FecG ) located on OAR5 [14], [21], [22] and BMP15 gene ( FecX ) located on the X chromosome [13], [14], [15], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have indicated that LS and OR can be genetically determined by the action of single genes with a major effect, named fecundity (Fec) genes [38]. All the three Fec genes discovered so far belong to the TGFß superfamily: BMPR1B gene ( FecB ) located on OAR6 [18], [19], [20], GDF9 gene ( FecG ) located on OAR5 [14], [21], [22] and BMP15 gene ( FecX ) located on the X chromosome [13], [14], [15], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of non-coding SNPs as causal mutations contrasts with other known mutations affecting ovulation rate through alteration of the coding sequence of BMP15 , GDF9 and BMPR1B genes impairing the protein function [10]. To go further in the fine mapping study, different strategies can be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, plasma concentrations of Follicle Stimulating Hormone (FSH) were not different compared to wild-type ewes. Based on ovarian phenotype and endocrine profiles, these findings suggest that the FecL L mutation affects ovarian function in a different way compared to other known hyperprolificacy-associated mutations, all affecting genes of the bone morphogenetic protein signaling system, BMP15 , GDF9 and BMPR1B [1], [10].…”
Section: Introductionmentioning
confidence: 91%
“…For instance, sheep prion diseases have been virtually eradicated by selecting rams carrying the ARR allele and selecting against the VRQ allele to the PRNP gene involved in resistance to scrapie (Sidani et al, 2010). To increase the meat yield of sheep flocks, the major prolificity genes (Vinet et al, 2012) have also been introgressed or selected in some sheep breeds worldwide.…”
Section: Use Of Cross-bred Animalsmentioning
confidence: 99%